The Influence of Classical Arabic for Violent Animated Cartoons on the Child's Verbal Communication - KOUIDER, Abdelwahab (My University, 2022)
The current research aims to determine the role of a classical Arabic for violent animated cartoons in verbal communication while acquiring non-standard Arabic language. This research work builds on the following question: To what extent does a classical Arabic for violent animated cartoons negatively impact the child's verbal communication? To answer the research question, the work urges socio-psycholinguistic quantitative analysis. Consequently, a quantitative research design has been adopted where the interview and questionnaire are the methods that have been applied in a descriptive framework as data collection tools. The sample is selected in fifth-year level from primary school Al-Mujahid Subih Mohammad -Relizane. Twenty children were interviewed and twenty questionnaires were received to their mothers. The study uses the interactionist language acquisition theory as the data analysis tool. The findings of this study have revealed that the child does moderately relate to violent cartoons. The animated cartoon classical Arabic language affects the child's verbal communication relatively. The relationship between the classical Arabic language for violent animated cartoons on the child‟s verbal communication is directly proportional. Finally, this type of research is one of the studies in socio-psycholinguistics, a topic for awareness-raising, and a reference point for many future studies by socio-psycholinguists.
A Case Study of the Fifth Year of Algerian Children, Al-Mujahid Subih Mohammad Primary School -Relizane
Keywords: psycholinguistics; language acquisition; interactionist theory; cartoons; communicative competence